Direct and indirect effect of 10 valent pneumococcal vaccine on nasopharyngeal carriage in children under 2 years of age in Matiari, Pakistan. Issue 8 (22nd February 2021) - Nisar, Muhammad Imran; Ahmed, Sheraz; Jehan, Fyezah; Shahid, Shahira; Shakoor, Sadia; Kabir, Furqan; Hotwani, Aneeta; Munir, Sahrish; Muhammad, Sajid; Khalid, Farah; Althouse, Benjamin; Hu, Hao; et al.
Abstract: Background: Pakistan introduced Ten-valent pneumococcal-conjugate-vaccine PCV10 in 2012 as a 3 + 0 schedule without catch-up. Methods: Children <2 years old in Matiari, Sindh provided nasopharyngeal swabs between 2014 and 2018, which were cultured for pneumococcus and serotyped through multiplex PCR at the Aga Khan University Hospital. Carriage rates over time for Vaccine-Type (VT) and Non-VT (NVT) serotypes were used to estimate direct, indirect, total and overall effects of vaccination. Regression analysis was used to determine factors associated with VT carriage. Results: Pneumococcus was detected in 2370/3140 (75%). VT carriage decreased overall, 16.1–9.6% (p-trend <0.001); vaccinated (all 3 doses of PCV10 received) 11.3–8.1% (p-trend 0.031) and unvaccinated (no PCV10 dose received) 17.4–10.3% (p-trend 0.003) with a decline in serotypes 6B, 9V/9A and 19F. Immunization increased from 41.0% to 68.4% (p-trend 0.001). Direct effect of vaccine was 32.8% (95% CI 14.7–47.0%) and indirect effect 44.6%(95% CI 40.6–48.6%). Factors associated with decreased VT colonization were education 1–5 years (aOR 0.7, 95%CI 0.6–1.0), history of difficulty breathing (aOR 0.7, 95%CI 0.5–1.0), exposure to smoke (aOR 0.8, 95% CI 0.6–1.0), child fully immunized (aOR 0.7, 95%CI 0.5–1.0) and enrolled in 3rd (aOR 0.6, 95%CI 0.4–0.8) and 4th (aOR 0.6, 95%CI 0.5–0.9) year of the study whereas history of runny nose (aOR 1.5, 95% CI 1.2–1.9) was positively associated. Conclusions: Decrease in VT pneumococcal carriage in vaccinated and unvaccinated children indicates herd immunity. Sustained increase in vaccine coverage and close long-term surveillance is warranted.